Dentin hypersensitivity after teeth bleaching with in-office systems. randomized clinical trial - Martin, Javier; Fernandez, Eduardo [UNESP]; Bahamondes, Valeria; Werner, Andrea; Elphick, Klaus; Oliveira, Osmir Batista [UNESP]; Moncada, Gustavo (My University, 2013)
Purpose: To comparatively and prospectively compare in a randomized clinical trial, dentin hypersensitivity after treatment with three in-office bleaching systems, based on hydrogen peroxide at different concentrations, with and without light source activation. Methods: 88 individuals were included according to inclusion and exclusion criteria. Subjects were randomly divided into the following three treatment groups: Group 1 was treated with three 15-minute applications of hydrogen peroxide at 15% with titanium dioxide (Lase Peroxide Lite) that was light-activated (Light Plus Whitening Lase) with five cycles of 1 minute and 30 seconds each cycle, giving a total treatment time of 45 minutes; Group 2 was treated with three 10-minute applications of hydrogen peroxide at 35% (Lase Peroxide Sensy), activated by light (LPWL) same activation cycles than Group 1, with a total treatment time of 30 minutes; Group 3 was treated with only one application for 45 minutes of hydrogen peroxide at 35% (Whitegold Office) without light activation. Each subject underwent one session of bleaching on the anterior teeth according to the manufacturers' instructions. Dentin sensitivity was recorded with a visual analogue scale (VAS) at baseline, immediately after, and at 7 and 30 days after treatment using a stimulus of an evaporative blowing triple syringe for 3 seconds on the upper central incisors from a distance of 1 cm. A Kruskal-Wallis test followed by Mann-Whitney test was performed for statistical analysis. Results: All groups showed increased sensitivity immediately after treatment. Group 1 displayed less changes relative to baseline with no significant differences (P= 0.104). At 7 and 30 days after treatment, a comparison of VAS values indicated no significant differences between all groups (P= 0.598 and 0.489, respectively).
Keywords: hydrogen peroxide; photosensitizing agent; titanium; titanium dioxide; tooth bleaching agent; adolescent; adult; comparative study; controlled clinical trial; controlled study; dental procedure; dentin sensitivity; diode laser; double blind procedure; female; follow up; human; male; methodology; pain assessment; photochemotherapy; phototherapy; prospective study; randomized controlled trial; time; Adolescent; Adult; Dentin Sensitivity; Double-Blind Method; Female; Follow-Up Studies; Humans; Hydrogen Peroxide; Lasers, Semiconductor; Male; Pain Measurement; Photochemotherapy; Photosensitizing Agents; Phototherapy; Prospective Studies; Time Factors; Titanium; Tooth Bleaching; Tooth Bleaching Agents; Young Adult